A companion to Birgitta of Sweden and her legacy in the later Middle Ages
1 online resource.
Keywords: St. Birgitta of Sweden (d. 1373) is one of the most celebrated female visionaries and authors of the Middle Ages and a central figure in the history of late-medieval religion. An aristocratic widow, Birgitta left her native country in 1349 and settled in Rome, where she established herself as an outspoken critic of the Avignon Papacy and an advocate of spiritual and ecclesiastical reform. Birgitta founded a new monastic order, and her major work, The Heavenly Book of Revelations, circulated widely in a variety of monastic, reformist, and intellectual milieus following her death. This volume offers an introduction to the saint and the reception of her work written by experts from various disciplines. In addition to acquainting the reader with the state of the scholarship, the study also presents fresh interpretations and new perspectives on Birgitta and the sources for her life and writings. Contributors: Roger Andersson, Nirit Ben-Aryeh Debby, Unn Falkeid, Anna Fredriksson, Birgitta Fritz, Ann M. Hutchison, F. Thomas Luongo, Maria H. Oen, Anders Piltz, and Pavlína Rychterová.